EFFECT OF TURMERIC (Curcuma longa) POWDER ON PRODUCTION PERFORMANCE AND EGG QUALITY CHARACTERISTICS OF LAYING HEN - A. Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An experiment was conducted to study the effect of turmeric powder on production performance and egg quality characteristics of Rhodo White (RW) layers. Seventy two RW layers were weighed individually and distributed randomly into four turmeric powder supplemented reated experimental diets with three replicates of six layers each and the experimental diet was given for a period of 20 weeks from 26 to 45 weeks age of the birds. There was no significant difference in total egg production, hen day egg production (HDEP) and hen housed egg production (HHEP) among the treatment groups. The feed intake in all treatment groups was almost similar during 26 to 45 weeks of birds. Turmeric powder did not inÀuence the feed intake and feed efficiency in all treatment groups. A non-significant difference was observed in egg quality characteristics. The egg yolk cholesterol was significantly (P